Social and Legal Norms Ensuring the Child’s Right to Live and be Brought up in a Family - SAGALAEVA, Evgenia Sergeevna; IVAHNENKO, Svetlana Nikolaevna; LANDINA, Olga Viktorovna (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The research is concerned with the analysis of social relations emerging in connection with the identification and arrangement of orphans and children left without parental care. The dynamics of regional statistical data as of 2016 and 2017 on the number of children left without parental care, the ratio of the reasons for the loss of parental care, the data on the forms of organization of such children, and the quantitative indicators of the arrangement in the substitute family of adoptive parents (including foreign), guardians, adoptive parents, or in a specialized institution are considered. The compliance of Russian legislation with international law in ensuring the protection of children deprived of parental care is assessed. The directions of the Russian state policy reflected in the relevant programs and strategies are analyzed. The scientific novelty of the work is manifested in the attempt to justify on the basis of the study of statistical indicators the relationship of social attitudes adopted in Russian society with the most constructive solution to the problem of orphanhood, including through legal regulation of relevant relations, and the need to provide not only financial but also other assistance to families.